Trade and Exchange Archaeological Studies from History and Prehistory - Dillian, Carolyn D.; White, Carolyn L.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Long before the advent of the global economy, foreign goods were transported, traded, and exchanged through myriad means, over short and long distances. Archaeological tools for identifying foreign objects, such as provenance studies, stylistic analyses, and economic documentary sources reveal non-local materials in historic and prehistoric assemblages. Trade and exchange represent more than mere production and consumption. Exchange of goods also led to an exchange of cultural and social experiences. Discoveries of the sources of alien objects surpass archaeological expectations of exchange and geographic distance, revealing important technological advances. With thirteen case studies from around the world, this comprehensive work provides a fresh perspective on material culture studies. Evidence of ongoing negotiation between individuals, villages, and nations provides insight into the impact of trade on the micro-, meso-, and macro-level. Covering a wide array of time periods and areas, this work will be of interest to archaeologists, anthropologists, and anyone working in cultural studies.
Introduction: Perspectives on Trade and Exchange -- Prehistoric Exchange -- Long-Distance Exchange of Obsidian in the mid-Atlantic United States -- Ulua Marble Vases Abroad: Contextualizing Social Networks Between the Maya World and Lower Central America -- Exotic Goods, Chivay Obsidian, and Sociopolitical Change in the South-Central Andes -- The Supply of Stone to the City of Rome: A Case Study of the Transport of Anician Building Stone and Millstone from the Santa Trinità Quarry (Orvieto) -- Interaction and Exchange Across the Transition to Pastoralism, Lake Turkana, Kenya -- Historic Exchange -- Beholden to Foreign Countries: Trade and Clothing in Portsmouth, New Hampshire -- The Precarious Middle Ground: Exchange and the Reconfiguration of Social Identity in the Hawaiian Kingdom -- Foreign Objects With Domestic Meanings: The Feast of Lanterns and the Point Alones Village -- What if the Local is Exotic and the Imported Mundane? -- When the Foreign is not Exotic: Ceramics at Colorado s WWII Japanese Internment Camp -- Discussion -- The Exotic in Daily Life: Trade and Exchange in Historical Archaeology -- Exchange Systems in Prehistory.
Keywords: Social sciences; Humanities; Anthropology; Archaeology; Social Sciences; Archaeology; Anthropology; Cultural Heritage